Regular yoga exercises and quality of life in women with low back pain - a pilot study - Joanna Lewandowska; Łukasz Pawik; Malwina Pawik; Felicja Fink-Lwow; Krystian Kałużny; Anna Kałużna; Walery Żukow (Kazimierz Wielki University, 2018)
Back pain symptoms are one of prevailing disfunctions that determine lowering quality of life and functioning in work environment becoming not only a health problem, but also a social problem in developed countries. In available literature yoga exercises are more and more indicated as a method of leveling low back pain. The aim of this pilot study was to assess the effectiveness of 8-week yoga exercises on quality of life and back pain symptoms by it's location and intensity in women with normal and excessive body weight. Twenty seven women completed both surveys (preliminary and evaluation), and systematically took part in yoga exercises for 8 weeks. The duration of a single yoga class was 45-60 minutes long. Yoga exercise program required attending to a conducted yoga classes (ashtanga yoga, yin yoga, hatha yoga, vinyasa yoga and yoga for hips and spine), at least twice a week for two months. After 8 weeks 92,59% of participants of program declared noticeable reduce in back pain intensity related to yoga exercises (including 22,22% of complete pain relief). Pain in the lumbar region of the spine was still dominating after 8 weeks (55,56%). It was observed that the majority of the SF-36 health domains scores increased values after 8-week yoga program, what could be related to the reduce of back pain intensity. After 8-week yoga program decrease in mean values of body mass were observed, however these changes were not statistically significant. Two-month yoga intervention may be recommended as a complementary physiotherapeutic method in low back pain treatment as well as to improve the quality of life for women. The relationship between yoga and prevention of obesity requires further research on larger group and the impact of obesity phenotypes is needed to be investigated.